2016
DOI: 10.1037/hea0000403
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and psychosocial correlates of objectively measured physical activity among older adults.

Abstract: Results highlighted that the perceived built environment is important for physical activity and sedentary behavior, largely because these environmental perceptions are positively linked to older adults' confidence in walking. By integrating environmental and psychosocial correlates of preventive health behaviors within a theoretical structure, the psychosocial mechanisms through which the environment affects activity can be better understood. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
(81 reference statements)
0
17
0
1
Order By: Relevance
“…The purpose of this study was to integrate perceived worksite neighbourhood walkability with the TPB to predict transport‐related walking in Chinese employees using a longitudinal design. As per the tenets of the TPB and previous research (McEachan et al., ; Rhodes et al., ), it was hypothesised that (a) attitudes, subjective norm, and PBC would directly predict intention and indirectly predict walking through intention (Ajzen, , ); (b) perceived worksite neighbourhood walkability would indirectly predict walking through the TPB constructs (Fleig et al., ; Rhodes et al., ); and (c) perceived worksite neighbourhood walkability would moderate the intention–walking relationship in line with the “augmenting hypothesis” (Rhodes et al., ). The proposed model of perceived worksite neighbourhood walkability, the TPB constructs, and transport‐related walking is detailed in Figure .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The purpose of this study was to integrate perceived worksite neighbourhood walkability with the TPB to predict transport‐related walking in Chinese employees using a longitudinal design. As per the tenets of the TPB and previous research (McEachan et al., ; Rhodes et al., ), it was hypothesised that (a) attitudes, subjective norm, and PBC would directly predict intention and indirectly predict walking through intention (Ajzen, , ); (b) perceived worksite neighbourhood walkability would indirectly predict walking through the TPB constructs (Fleig et al., ; Rhodes et al., ); and (c) perceived worksite neighbourhood walkability would moderate the intention–walking relationship in line with the “augmenting hypothesis” (Rhodes et al., ). The proposed model of perceived worksite neighbourhood walkability, the TPB constructs, and transport‐related walking is detailed in Figure .…”
Section: Introductionmentioning
confidence: 89%
“…The first pathway is that the TPB constructs are considered to be proximal predictors of health behaviours, which suggests that external variables, such as the neighbourhood environment, are mediated by the TPB constructs in explaining intention and PA. Evidence indicates that attitude, subjective norm, and PBC may mediate these relationships as hypothesised in this pathway (Fleig et al., ; Rhodes et al., ). For example, PBC mediated the association between perceived street connectivity and land‐use diversity with objectively measured PA among a Canadian sample (Fleig et al., ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Se encontró relación negativa entre la percepción de la conectividad de la calle y el uso del suelo mixto con el comportamiento sedentario; del mismo modo, hubo relación entre los efectos de la conectividad de la calle y el uso de suelo sobre la AF. Los resultados mostraron la importancia que tiene la percepción del entorno físico con la AF y el comportamiento sedentario, en gran parte debido a que estas percepciones ambientales están vinculadas de manera positiva a la confianza para caminar (84) .…”
Section: Actividad Física Y Entornosunclassified
“…However, in recent years, the ‘mobility turn’ has expanded this approach by arguing that in addition to physical movement – getting from one place to another – mobility is characterised by the representations of movement that give it a shared meaning and the experiences and embodied practice of movement (Cresswell 2010; Frello 2008). These subjective facets affect older adults’ judgements and actions, and have a significant impact on why older adults choose to physically move themselves throughout their communities (Chudyk et al 2015; Fleig et al 2016; Goins et al 2014; Mokhtarian, Salomon and Singer 2015; Mollenkopf, Hieber and Wahl 2011; Rantakokko et al 2014; Ziegler and Schwanen 2011). For example, Ziegler and Schwanen (2011) found that an ‘openness to engagement’, defined as a mental disposition of willingness to connect with the world, is a crucial driver of mobility and wellbeing.…”
Section: Introductionmentioning
confidence: 99%